'The blue one takes a battering' why do young adults with asthma overuse bronchodilator inhalers? A qualitative study. Issue 2 (19th February 2013) - Cole, Sue; Seale, Clive; Griffiths, Chris
Abstract : Objective: Overuse of short-acting bronchodilators is internationally recognised as a marker of poor asthma control, high healthcare use and increased risk of asthma death. Young adults with asthma commonly overuse short-acting bronchodilators. We sought to determine the reasons for overuse of bronchodilator inhalers in a sample of young adults with asthma. Design: Qualitative study using a purposive extreme case sample. Setting: A large urban UK general practice. Participants: Twenty-one adults with moderate asthma, aged 20–32 years. Twelve were high users of short-acting bronchodilators, nine were low users. Results: Asthma had a major impact on respondents' lives, disrupting their childhood, family life and career opportunities. High users of short-acting bronchodilators had adapted poorly to having asthma and expressed anger at the restrictions they experienced. Overuse made sense to them: short-acting bronchodilators were a rapid, effective, cheap 'quick-fix' for asthma symptoms. High users had poorer control of asthma and held explanatory models of asthma which emphasised short-term relief via bronchodilation over prevention. Both high and low users held strong views about having to pay for asthma medication, with costs cited as a reason for not purchasing anti-inflammatory inhalers. Conclusions: Young adults who were high users of short-acting bronchodilators had adapted poorly to having asthma and had poor asthma control. They gave coherent reasons for overuse. Strategies that might address high bronchodilator use in young adults include improving education to help young people accept and adapt to their illness, reducing stigmatisation and providing free asthma medication to encourage the use of anti-inflammatory inhalers.